An Immuno-Cardiac Model for Macrophage-Mediated Inflammation in COVID-19 Hearts. Issue 1 (15th April 2021) - Yang, Liuliu; Han, Yuling; Jaffré, Fabrice; Nilsson-Payant, Benjamin E.; Bram, Yaron; Wang, Pengfei; Zhu, Jiajun; Zhang, Tuo; Redmond, David; Houghton, Sean; Uhl, Skyler; Borczuk, Alain; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Rationale: While respiratory failure is a frequent and clinically significant outcome of coronavirus disease 2019 (COVID-19), cardiac complications are a common feature in hospitalized COVID-19 patients and are associated with worse patient outcomes. The cause of cardiac injury in COVID-19 patients is not yet known. Case reports of COVID-19 autopsy heart samples have demonstrated abnormal inflammatory infiltration of macrophages in heart tissues. Objective: Generate an immunocardiac coculture platform to model macrophage-mediated hyperinflammation in COVID-19 hearts and screen for drugs that can block the macrophage-mediated inflammation. Methods and Results: We systematically compared autopsy samples from non–COVID-19 donors and COVID-19 patients using RNA sequencing and immunohistochemistry. We observed strikingly increased expression levels of CCL2 (C-C motif chemokine ligand 2) and macrophage infiltration in heart tissues of COVID-19 patients. We generated an immunocardiac coculture platform containing human pluripotent stem cell–derived cardiomyocytes and macrophages. We found that macrophages induce increased reactive oxygen species and apoptosis in cardiomyocytes by secreting IL (interleukin)-6 and TNF-α (tumor necrosis factor alpha) after Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) exposure. Using this immunocardiac coculture platform, we performed a high content screen and identified ranolazine and tofacitinib as compounds that protect cardiomyocytes from macrophage-induced cardiotoxicity. Conclusions: We established an immuno-host coculture system to study macrophage-induced host cell damage following SARS-CoV-2 infection and identified Food and Drug Administration–approved drug candidates that alleviate the macrophage-mediated hyperinflammation and cellular injury.